2011
DOI: 10.1029/2010jg001456
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Asian dust with chlorophyll and primary productivity in the coastal seas of China during the period from 1998 to 2008

Abstract: Satellite chlorophyll a (Chl a) concentrations and estimated primary production in the coastal seas of China were correlated with Asian dust events during 1998–2008. Dust events were identified using two approaches, i.e., historical record and satellite aerosol index (AI). Severe and very severe dust events correlated well and positively with Chl a concentrations and primary production in the south Yellow Sea and East China Sea, but it was not statistically significant in the Bohai Sea and the north Yellow Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 33 publications
4
62
0
Order By: Relevance
“…In addition, the annual dust input to the entire ECS is estimated to be 17 Mt, which appears to be a significant source of sediments and dissolved Fe compared with riverine discharge (Hsu et al, 2009). Tan et al (2011) also found that chl a and primary production increased and eventually became a bloom 1-21 days after the occurrence of dust storms in the southern YS. It would be worth investigating the longterm trends of dust input when such data become available in the future.…”
Section: Nutrient Supply In Region Bmentioning
confidence: 95%
“…In addition, the annual dust input to the entire ECS is estimated to be 17 Mt, which appears to be a significant source of sediments and dissolved Fe compared with riverine discharge (Hsu et al, 2009). Tan et al (2011) also found that chl a and primary production increased and eventually became a bloom 1-21 days after the occurrence of dust storms in the southern YS. It would be worth investigating the longterm trends of dust input when such data become available in the future.…”
Section: Nutrient Supply In Region Bmentioning
confidence: 95%
“…A suitable chlorophyll index can offer useful information for estimating the gross productivity of a terrestrial ecosystem (Nave et al, 2011) and even for understanding dust storm events (Tan et al, 2011). In order to address the effects of global climate changes, it is necessary to continuously update the prediction of forest carbon sequestration and the net primary productivity of terrestrial ecosystem.…”
Section: Indexmentioning
confidence: 99%
“…4(a). High aerosol loading and water reflectance conditions are occurred due to the transportation from inland pollutant as a result of increase of oceanic substances or primary productivity (Tan et al, 2011). The retrieved Chl and sediment concentrations are mostly higher than those of other sites with averaged 25 Chl and S s up to 2.16 mg m -3 and 1.75 g m -3 in this study, since the location of this site is typically viewed as high turbid waters.…”
Section: Using Satellite Measurements Out Of Sun Glintmentioning
confidence: 72%